Análise de Helicobacter pylori na placa dental e saliva e biópsia gástrica - Monteiro, Rosimere dos Santos Bastos (2004)
Helicobacter pylori is a gram-negative bacterium, mobile, microaerophilic, associated with chronic gastritis, peptic ulcers, duodenal ulcers and consists of a risk factor for gastric cancer. The objective of this study was to evaluate the presence Helicobacter pylori in gastric biopsy samples, dental plaque and Saliva samples are collected from 26 subjects in this study were be examined by endoscopy. The colonization of this bacterium in biopsy Gastric was assessed by using three detection methods: histological analysis, rapid urease test and PCR method. For the detection of Helicobacter pylori Dental plaque and saliva was used the PCR method. In the PCR reaction was used a pair of synthetic primer-gene 16S r-RNA Helicobacter pylori: the HP1 primer: 5'-TGGAATCAGCGTCAGGTAATG-3 'and primer HP2: 5'- GCTAAGAGATCAGCCTATGTCC -3 '. The PCR amplification product was detected by electrophoresis on 1.5% agarose gel. First, it performed gastroscopy which ranked the 26 patients into two groups: 20 with gastric inflammation (pangastritis) and 6 considered normal. Then, the 20 Gastric biopsies of subjects with pangastritis were subjected to the three Helicobacter pylori detection methods selected for this study. THE Histopathological analysis identified 15 positive individuals Helicobacter pylori (75%, 15/20), rapid urease test identified 14 individuals (70%, 14/20) and PCR method identified 17 patients (85%, 17/20). The samples of dental plaque and the saliva, by PCR method suggests the absence of the bacterium Helicobacter pylori. Results from Helicobacter pylori detection methods in gastric samples from 6 subjects with no gastric inflammation resulted in a 17% (1/6) for histopathology, 33% (2/6) for the rapid urease test and 67% (4/6) for the PCR method. The PCR analysis in samples of dental plaque and saliva of these 6 patients suggests the absence of Helicobacter pylori. The presence of Helicobacter pylori was detected in gastric biopsies by histological methods, rapid urease test and PCR, the latter method had a higher sensitivity. The PCR analysis in dental plaque and saliva showed no presence of H. pylori in the population studied.